Key parameter influence mechanism and optimal working fluid screening correlation for trans-critical organic Rankine cycle with open type heat sources. (1st January 2021) - Huixing, Zhai; Lin, Shi; Qingsong, An; Suilin, Wang; Baolin, An
Abstract: Trans-critical organic Rankine cycles (ORC) are promising for low to medium temperature heat recovery. To achieve a better cycle performance, the screening of optimal working fluids is quite significant. The optimal working fluids vary with the heat sources, working conditions and performance criterion, and it is difficult to build a general optimal working fluid screening criterion for the trans-critical ORC. Finding the relationship between the working fluid thermodynamic properties and the cycle performance is an effective way to establish general method for optimal working fluid screening. This paper provides theoretical analysis of how the key working fluid thermodynamic properties influence on the cycle performance under a wide temperature range of open type heat sources using various working fluids. Especially the influence of 'uniformity of c p ' on the heat source utilization is originally analysed. In addition, a relatively general quantitative correlation for selecting the optimal working fluid for trans-critical ORC with heat source temperatures from 150 to 350 °C is presented. Highlights: How 'uniformity of c p ' influences heat source utilization is originally analysed. T c having decisive influence on trans-critical ORC performance is firstly proposed. Influence of working fluid dryness on ORC with open type heat sources is studied. A quantitative correlation is firstly provided for quick working fluid screening.